Impact Analysis of the Use of IoT Technology and Environmental Monitoring Systems on Waste Reduction in the Food and Beverage Industry in Indonesia - Bakhar, Muhamad; Budihartono, Eko (Westscience Press, 2023)
The present research endeavors to examine the effects of IoT technology and environmental monitoring systems on waste reduction within Indonesia's food and beverage sector. Using a sample of 250 participants, a thorough study was carried out while accounting for the size, location, and kind of operation of the organization. Discriminant validity was verified after the measurement model underwent a thorough evaluation for validity and reliability. Tests of statistical significance demonstrated how important IoT technology and environmental monitoring systems are in affecting waste reduction. The model's significant explanatory and predictive power is demonstrated by the R-Square and Q2 values, while the model fit index highlights the estimated model's suitability. The results offer significant perspectives for industry participants and policy officials who seek to enhance sustainability measures in Indonesia's food and beverage industry.